Integrating Medicinal Plant Cultivation Into Agroforestry Systems For Biodiversity And Income Generation - Kholiya, Deepak; Uttam, Lad Dhairyashil; Rajan, Priyanka; Sharma, Sarah; Manjeet, Manjeet; Jain, Gaurav; Bhandari, Ambika; Pal Kaur, Dinanter (Journal of Neonatal Surgery, 2025)
Agroforestry, the deliberate integration of trees and shrubs into agricultural landscapes, has gained recognition for its ability to enhance ecosystem services, promote biodiversity, and improve rural livelihoods. With the growing global demand for medicinal plants, the integration of these plants into agroforestry systems provides a sustainable land-use solution that addresses both ecological and socio-economic challenges. This study explores the impact of medicinal plant cultivation within agroforestry systems on biodiversity and income generation in rural India. Focusing on three agro-ecological zones—Himachal Pradesh, Odisha, and Madhya Pradesh—this research evaluates the effects of medicinal plant integration on biodiversity indices, soil health, and farmer income over a two-year period. The study found that agroforestry systems incorporating medicinal plants exhibited significantly higher species richness, improved biodiversity indices, and enhanced soil health compared to control systems. Additionally, farmers practicing medicinal agroforestry achieved higher yields and income, with notable profitability from high-demand species like Withania somnifera (Ashwagandha) and Ocimum sanctum (Tulsi). Despite these positive outcomes, challenges such as limited market access, insufficient technical knowledge, and inadequate policy support remain. The study concludes by recommending policies that support market linkages, provide technical training, and create incentives for medicinal plant cultivation within agroforestry systems to enhance biodiversity conservation and rural income generation.